Moral disengagement and callous–unemotional traits: A longitudinal study of Italian adolescents with a disruptive behaviour disorder. (13th September 2016) - Muratori, Pietro; Paciello, Marinella; Buonanno, Carlo; Milone, Annarita; Ruglioni, Laura; Lochman, John E.; Masi, Gabriele
Abstract: Background: Callous–unemotional traits have been proposed as risk factors for a poorer prognosis in young people with disruptive behaviour disorders. Identification of factors that may cause or maintain elevated levels of such traits could help in developing targeted therapeutic interventions. Some previous studies have investigated the role of moral cognitive mechanisms, such as moral disengagement, but these previous studies focused primarily on normal or 'at‐risk' samples. Aim: We aimed to evaluate associations and possible interactions between moral disengagement as a cognitive dimension and callous–unemotional traits as an affective dimension in adolescents with disruptive behaviour disorders. Method: We recruited 55 adolescents with a disruptive behaviour disorder from a community care hospital in Pisa. They were evaluated at baseline and after one year with measures that included a moral disengagement scale, the Antisocial Process Screening Device, to assess callous traits, and the Youth Self‐Report, to explore externalising behaviour problems. Results: Structural equation modelling showed that higher initial moral disengagement scores were associated with later higher levels of callous–unemotional traits in adolescents and vice versa, even after, respectively, controlling for previous levels of callous traits and moral disengagement. Conclusion: As impairments in either cognitive or affective traits may predispose to problematic development of the other, our findings would suggest that screening at the earliest opportunity possible for both moral disengagement and callous–unemotional traits among children with disruptive behaviour disorders could help to map natural outcome pathways and thus tailor more accurate interventions for prevention of antisocial or criminal behaviour. Copyright © 2016 John Wiley & Sons, Ltd.